(untitled) (Al-Academy, 2025)
The research explores the concept of intertextuality in contemporary visual art, focusing on the aesthetics of composition and the openness to interpretation. It aims to shed light on the concept of intertextuality and key theoretical approaches that have introduced this critical term. The study addresses the problem of intertextuality and its role in revealing symbolic meanings and understanding the visual vocabulary of contemporary artworks through a semiotic-intertextual approach. The goal is to comprehend the relationship between visual intertextuality and the dynamics of artistic creation, as well as the role of the viewer in activating it. The study emphasizes the uniqueness of each artwork and its contemporary implications. Considering that a painting is a multi-layered visual text subject to intertextual connections, the research concludes that paintings exhibit a chemistry where their variables dynamically interact in the equation of formation and interpretation123